Participation as the Central Axis of Development - Flor, Eulalia (2019)
This article aims at showing the development of a still ongoing historical shift in the relationship between civil society and the State, through social citizen’s participation in the formulation and execution of public policy, from which even a new model of governance could be yielded. Is in the Latin American experience where we can find such an experimental ‘laboratory’ in which opportunities of participation are constantly furnished. It is concluded that this is a complex and, in certain moments, even confrontation-laden interaction, in which the ‘conventional’ States cannot easily adapt and smoothly process to the constant presence of social groups and their claims, nor the latter can re-accommodate to this novel fluid interaction with established power. This presents a paradox since no strategy of development could be devised without taking as one of its essential elements, the effective participation of civil society.